2018
DOI: 10.1186/s12889-018-5363-3
|View full text |Cite
|
Sign up to set email alerts
|

Under-estimation of maternal and perinatal mortality revealed by an enhanced surveillance system: enumerating all births and deaths in Pakistan

Abstract: BackgroundReliable and timely data on maternal and neonatal mortality is required to implement health interventions, monitor progress, and evaluate health programs at national and sub-national levels. In most South Asian countries, including Pakistan, vital civil registration and health information systems are inadequate. The aim of this study is to determine accurate maternal and perinatal mortality through enhanced surveillance of births and deaths, compared with prior routinely collected data.MethodsAn enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 32 publications
4
22
0
1
Order By: Relevance
“…This could be due to the reason that: if pregnancy surveillance is active, every stakeholder like; women development group (WDG) and steering committee could be active to attend the pregnancy outcome of each registered pregnant mothers. This finding is supported by a study from Pakistan which revealed that higher mortality detection by enhanced pregnancy surveillance system [47].…”
Section: Discussionsupporting
confidence: 67%
“…This could be due to the reason that: if pregnancy surveillance is active, every stakeholder like; women development group (WDG) and steering committee could be active to attend the pregnancy outcome of each registered pregnant mothers. This finding is supported by a study from Pakistan which revealed that higher mortality detection by enhanced pregnancy surveillance system [47].…”
Section: Discussionsupporting
confidence: 67%
“…Birth weight below 2.5 kg was found in 26(60.5%) babies in our study. Low birth weight is an important cause of death, as observed in other studies 3,15 . The factors responsible for these can be identified during the antenatal period; most of these can present with conditions that may be associated with low birth weight.…”
Section: Table 1: Distribution Of Deliveries In Perinatal Mortality In One Year Periodsupporting
confidence: 56%
“…Serial data from demographic health surveys conducted in Pakistan shows a NMR of 55 deaths per 1,000 live births between 1992 to 2012 which improved to 42 deaths per 1,000 live births in the most current 5-year period (14,15). This minimal improvement shown was even challenged by research that shows that neonatal mortality rates in the study area were under-estimated by 50% (16).…”
Section: Introductionmentioning
confidence: 92%